Value Investing in Modern Times - Świercz, Wojciech; Szostak, Radosław (Inwestowanie wartościowe w dzisiejszych czasach, 2024)
The goal of this study is to examine the relevance of the value investing strategy in today’s dynamic market environment. The study provides the most valuable information about the value investing strategy, its assumptions, benefits, drawbacks, and results of the suggested strategy that is based primarily on Benjamin Graham’s approach to financial markets. The research is conducted by backtesting on, in total, a 5-year sample using a platform GuruFocus. The assumptions of the research are based on a literature review in the field of finance, usage of historical data, and calculation of the return rate from various variations of the strategy, as well as the computation of indicators such as Upside Potential Ratio, Downside Risk, and Omega. The work demonstrates that the value investing strategy remains a viable investment approach in today's market. The findings suggest that focusing on the financial fundamentals of companies and picking stocks, which are in accordance to conducted analysis undervalued, can still yield satisfactory investment results compared to the S&P500 main index. Investors should still consider using this somewhat old strategy, but they must be aware of the challenges and risks associated with investing.
Cytuj za: Świercz, W., Szostak, R. (2024). Value Investing in Modern Times. In M. Pauka, T. Słoński (Eds.), Finanse (pp. 79-95). Publishing House of Wroclaw University of Economics and Business.
Keywords: value investing; value investing principles; strategy verification; investment analysis; Benjamin Graham strategy; inwestowanie wartościowe; zasady inwestowania wartościowego; weryfikacja strategii; analiza inwestycyjna; strategia Benjamina Grahama